Adiponectin Gene Polymorphisms and Possible Susceptibility to Metabolic Syndrome among the Sudanese Population: A Case-Control Study - Altaf S. Mosad; Ghada A. Elfadil; Alsadig Gassoum; Khanssa M. Elamin; Nazik Elmalaika Obaid Seid Ahmed Husain (International Journal of Endocrinology)
Background and Aim. The adiponectin gene (ADIPQ) has been identified as a human adiposity marker of metabolic syndrome (MetS) in several ethnic cultures. This study aimed to determine the allelic genotypes and haplotypes distribution of the ADIPQ gene polymorphisms and its association with body mass index (BMI), waist circumference (WC), glycated hemoglobin (HbA1c), and lipid profile in MetS adult Sudanese patients. Methodology. Four hundred and twenty middle-aged adults participated in this community-based case-control research. BMI (kg/m2) and blood pressure (BP) were measured. HbA1c (%) and lipid profile evaluation was performed on fasting blood samples. The guanidine extraction procedure was used to extract genomic DNA from EDTA whole blood by using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP); samples were genotyped for the polymorphisms (rs266729), (rs2241766), and (rs1501299). Results. There is a significant difference in genotypic frequencies of the rs266729, rs2241766, and rs1501299 SNPs and allele frequencies P <0.05 between the MetS patients and non-MetS group. MetS patients had a significantly higher serum triglycerides (TG), total cholesterol (TC), and low-density lipoprotein-cholesterol (LDL-C) in the GG genotype of rs2241766 P <0.05. Additionally; the TT genotype of rs1501299 had higher SBP, serum TG, TC, and LDL-C P <0.05. Multivariate logistic regression analysis showed hypertension, hyperglycemia, BMI, WC, serum TG, ADIPOQ rs2241766 (TG allele), and ADIPOQ rs1501299 (GT allele) had independently predicted the incidence of metabolic syndrome in the Sudanese population. The three investigated SNPs of ADIPOQ were in a moderate linkage disequilibrium (LD) connection according to the LD measures (D' = 0.54, 0.62, and 0.69, respectively). The CTT, CGG, and GTG haplotypes, which consist of three alleles of −11377C > G, +45T > G, and +276G > T, were shown to report 1.788-, 1.622,- and 1.641-fold risks toward MetS susceptibility in Sudanese’s population, respectively. Conclusion. Along with clinical and biochemical signs, the ADIPOQ gene’s genetic variants (rs266729, rs2241766, and rs1501299), CTT, CGG, and GTG haplotypes are connected to the MetS risk among the Sudanese population.